2012
DOI: 10.1186/1476-0711-11-24
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibiotic susceptibility testing of Brucella isolates from Egypt between 1999 and 2007 and evidence of probable rifampin resistance

Abstract: BackgroundBrucellosis poses a significant public health problem in Mediterranean countries, including Egypt. Treatment of this disease is often empirical due to limited information on the antibiotic susceptibility profiles of Brucella spp. in this region of the world. The aim of this study was to determine the antibiotic susceptibility profiles of Brucella blood isolates in Egypt, a country endemic for brucellosis.MethodsBrucella spp. isolates were identified from the blood cultures of acute febrile illness (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
63
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 14 publications
10
63
2
Order By: Relevance
“…The main factor that preludes its wider use is probably the side effect and the parenteral mode of administration. In this study gentamicin showed a good in vitro activity against all the tested Brucella isolates as reported previously in other countries [18, 28, 33]. Similar finding [34] as well as lower [29] and higher [8] MIC values were reported in Turkey for gentamicin.…”
Section: Discussionsupporting
confidence: 89%
“…The main factor that preludes its wider use is probably the side effect and the parenteral mode of administration. In this study gentamicin showed a good in vitro activity against all the tested Brucella isolates as reported previously in other countries [18, 28, 33]. Similar finding [34] as well as lower [29] and higher [8] MIC values were reported in Turkey for gentamicin.…”
Section: Discussionsupporting
confidence: 89%
“…However, when compared with CLSI reference values for H.influenzae [8], in the present study, 48 % of Brucella strains showed elevated MIC’s of rifampicin (>1 mg/L). Higher MIC’s to rifampicin has been reported previously from Egypt (64 %) [9] and Malaysia (70 %) [15]. However, the impact of high MIC’s on clinical outcome in these countries is not known.…”
Section: Discussionmentioning
confidence: 86%
“…Antibiotics administrated were oral doxycycline and either intravenous gentamycin or oral rifampin. Multidrug antimicrobial regimens are the mainstay of therapy because of high relapse rates reported with monotherapeutic approaches …”
Section: Discussionmentioning
confidence: 99%